Acute Eosinophilic Ascites in a Middle-Aged Man - Fadi Bleibel; Keith Fragoza; Garrey T. Faller (Case Reports in Gastrointestinal Medicine)
Eosinophilic gastroenteritis is a rare condition characterized by recurrent eosinophilic infiltration of portions of the GI tract and presenting with nonspecific GI symptoms in association with peripheral eosinophilia. Its etiology and pathogenesis remain unclear and its symptoms overlap with many GI and systemic diseases. Thus, both gastroenterologists and general internists need to be aware of this rare condition. We present a case of a 55-year-old male with diffuse abdominal pain and distention for two weeks. His physical examination was significant for moderate ascites. Initial work-up demonstrated severe peripheral blood eosinophilia, normal liver function tests, thickening of the stomach and small bowel wall, and elevated serum IgE. Upper endoscopy and extensive testing for malignancy and parasitic infections failed to establish a diagnosis. Ascitic fluid analysis showed significant eosinophilia. Further, a full-thickness jejunal showed marked eosinophilic infiltration of the serosa and muscularis propria. Subsequent treatment with oral prednisone resulted in normalization of laboratory and radiologic abnormalities in a few week period.